The Psycho-Social Conditions of Asylum-Seekers from Darfur in Israel - Vered Slonim-Nevo; Shirley Regev; Yiftach Millo (Refuge, 2015)
Objective The study appraises the prevalence of pre-migration trauma exposure, the ability to secure basic living needs, and psychological functioning among Darfuri asylumseekers and refugees living in Israel.